PENGARUH MANAJEMEN KETATAUSAHAAN DAN KUALITAS PELAYANAN TERHADAP KEPUASAN SISWA DI MA AT-TAUFIQ BOGEM - Rahmawati, Mita; Suwandi (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2024)
Some of the objectives of this research are as follows: (1) Determine whether administrative management influences student satisfaction; (2) Determine whether service quality influences student satisfaction; and (3) Determine whether administrative management and service quality influence student satisfaction. A quantitative approach was taken in this research with the type of research using ex post facto. analyzing data using multiple linear regression tests. And the conclusions from the data obtained were: (1) Administrative management partially influences student satisfaction. It is known through hypothesis testing (in the form of a significance figure of 0.000 < 0.005 and the result of the T count is 4.767 < 1.997); (2) Service quality partially influences student satisfaction as proven by the results of the hypothesis test (the significant number is 0.000 < 0.005 and the T count is 4.764 < 1.997); (3) Administrative management and service quality simultaneously influence student satisfaction. It can be seen through the nominal significance, namely 0.000 < 0.005 and the calculated F result 15.042 < 2.74).